2013
DOI: 10.3390/md11072595
|View full text |Cite
|
Sign up to set email alerts
|

Lithothamnion muelleri Controls Inflammatory Responses, Target Organ Injury and Lethality Associated with Graft-versus-Host Disease in Mice

Abstract: Lithothamnion muelleri (Hapalidiaceae) is a marine red alga, which is a member of a group of algae with anti-inflammatory, antitumor, and immunomodulatory properties. The present study evaluated the effects of treatment with Lithothamnion muelleri extract (LM) in a model of acute graft-versus-host disease (GVHD), using a model of adoptive splenocyte transfer from C57BL/6 donors into B6D2F1 recipient mice. Mice treated with LM showed reduced clinical signs of disease and mortality when compared with untreated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…It is known that GVHD is also characterized by intestinal injury [ 41 44 ]. Intestinal injury is associated with bacterial translocation to the liver and subsequently into the bloodstream [ 25 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that GVHD is also characterized by intestinal injury [ 41 44 ]. Intestinal injury is associated with bacterial translocation to the liver and subsequently into the bloodstream [ 25 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications during 2012–2013 reported extracts or structurally uncharacterized marine compounds, with novel and interesting preclinical and/or clinical pharmacology: in vitro antimalarial activity in crude extracts from Fiji marine organisms using a semi-automated RNA fluorescence-based high-content live cell-imaging assay [10]; the first report of in vitro liver stage antiplasmodial activity and dual stage inhibitory potential of British seaweeds [11]; anti-hepatitis C virus activity affecting the viral helicase NS3 and replication, in crude extracts from the marine feather star Alloeocomatella polycladia [12]; anti-herpes simplex virus HSV-1 and HSV-2 activity in a purified sulfoglycolipid fraction from the Brazilian marine alga Osmundaria obtusiloba [13]; in vivo anti-inflammatory activity of a heterofucan from the Brazilian seaweed Dictyota menstrualis that inhibited leukocyte migration to sites of tissue injury by binding to the cell membrane [14]; in vivo antinociceptive and anti-inflammatory activity in a crude methanolic extract of the red alga Bryothamnion triquetrum [15]; in vivo anti-inflammatory activity in a sulfate polysaccharide fraction from the red alga Gracilaria caudata resulting in significant inhibition of neutrophil migration and cytokine release [16]; in vitro anti-inflammatory effect of a hexane-soluble fraction of the brown alga Laminaria japonica that inhibited nitric oxide, prostaglandin E 2 , interleukin (IL)-1β and IL-6 release from lipopolysaccharide-stimulated macrophages via inactivation of nuclear factor-κB transcription factor [17]; in vivo anti-inflammatory of a polysaccharide-rich fraction from the marine red alga Lithothamnion muelleri that reduced organ injury and lethality, as well as pro-inflammatory cytokines and chemokines, associated with graft-versus-host disease in mice [18]; in vivo clinical effectiveness in an osteoarthritis trial by PCSO-524 TM , a nonpolar lipid extract from the New Zealand marine green lipped mussel Perna canaliculus , which may offer “potential alternative complementary therapy with no side effects for osteoarthritis patients” [19]; enhanced antioxidant activity of chitosan nanoparticles as compared to chitosan on hydrogen peroxide-induced stress injury in mouse macrophages in vitro [20]; induction of concentration-dependent vasoconstrictive activity on isolated rat aorta by a tentacle extract from the jellyfish Cyanea capillata [21]; significant antioxidant effect of a sulfated-polysaccharide fraction of the marine red alga Gracilaria birdiae which prevented naproxen-induced gastrointestinal damage in rats by reversing glutathione depletion [22]; in vitro antioxidant properties of a polysaccharide from the brown seaweed Sargassum graminifolium (Turn.) that was also observed to inhibit calcium oxalate crystallization, a constituent of urinary kidney stones [23]; antioxidant activity in organic extracts from 30 species of Hawaiian marine algae, with the carotenoid fucoxanthin identified as the major bioactive antioxidant compound in the brown alga T. ornata [24]; screening of antioxidant activity in 18 cyanobacteria and 23 microalgae cell extracts identified Scenedesmus obliquus strai...…”
Section: Introductionmentioning
confidence: 99%
“…is commercialized as food supplements in different countries, as sources of calcium and other mineral components. The chemical composition of red alga also comprises large amounts of sulfated water-soluble polysaccharides, to which several anti-inflammatory properties were attributed [ 18 19 , 22 , 27 ]. The biological effects elicited by poly- and oligosaccharides depend on the nature of the constitutive monosaccharides as well as the stereochemistry of the linkages [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also demonstrated that L . muelleri treatment controls inflammatory responses, tissue injury and mortality associated with Graft- versus -Host disease via inhibition of leukocyte interactions with intestinal venules [ 22 ]. Altogether, we suggest here that the amelioration of arthritis in L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation